Lifestyle Intervention Involving Calorie Restriction with or without Aerobic Exercise Training Improves Liver Fat in Adults with Visceral Adiposity - Eiichi Yoshimura; Hideaki Kumahara; Takuro Tobina; Takuro Matsuda; Makoto Ayabe; Akira Kiyonaga; Keizo Anzai; Yasuki Higaki; Hiroaki Tanaka (Journal of Obesity)
Objective. To evaluate the effect of calorie restriction-induced weight loss with or without aerobic exercise on liver fat. Methods. Thirty-three adults with visceral adiposity were divided into calorie restriction (CR; n = 18) or CR and aerobic exercise (CR + Ex; n = 15) groups. Target energy intake was 25 kcal/kg of ideal body weight. The CR + Ex group had a targeted exercise time of 300 min/wk or more at lactate threshold intensity for 12 weeks. Results. Reductions in body weight (CR, -5.3 ± 0.8 kg; CR + Ex, -5.1 ± 0.7 kg), fat mass (CR, -4.9± 0.9 kg; CR + Ex, -4.4 ± 0.6 kg), and visceral fat (CR, -24 ± 5 cm2; CR + Ex, -37 ± 5 cm2) were not statistically different between groups. Liver fat decreased significantly in both groups, with no difference between groups. Change in maximal oxygen uptake was significantly greater in the CR + Ex group than in the CR group (CR, -0.7 ± 0.7 mL/kg/min; CR + Ex, 2.9 ± 1.0 mL/kg/min). Conclusion. Both CR and CR + Ex resulted in an improved reduction in liver fat; however, there was no additive effect of exercise training.